Remix, Mash-up, Share : Authentic Web 2.0 Assessment Scenarios and Criteria for Interactive Media, Games and Digital Design Final Report. - Richardson, Ingrid (Office for Learning and Teaching, 2013)
The proliferation of Web 2.0 applications and services has had a significant impact on university learning environments. However, much of the teaching and learning literature and research projects in this area have focused primarily on the integration of blogs, wikis and social networking systems into pedagogical practice. This is the final report from a project that focused on the emergence of a type of content production that is collaborative and shared and comprises the re-use and remixing of existing media content, or the blend and aggregation of existing services and applications. The project explored, in particular, the development of authentic assessment practices and criteria in the disciplines of interactive media, games and digital design. At June 2010, twelve of the devised 14 Web 2.0 assessment exemplars were implemented across 13 units within the three participating institutions during the first semester, 2010. A two-day workshop was held in Perth to bring together the project leader and four institutional project coordinators to brainstorm Web 2.0 ontology, assessment scenarios and exemplars. The team then commenced qualitative data collection and presented case studies for each exemplar at a second workshop in July 2010. A WordPress web interface, protected by a password, was created for the project. The project was presented at the Digital Life Forms II conference at Murdoch University in September 2010, and a Networks for Enhancing the Scholarship of Teaching (NEST) event in December 2010.